Development of an enhanced enzyme engineering framework towards improved ethylene productivity - Van Hagen, Alexander Marcus William (2020)
Fossil fuels are the primary feedstock for chemical and fuel production, yet they are unsustainable and have a deleterious impact on the environment. Ethylene is a small hydrocarbon gas. Its annual worldwide production currently exceeds 150 million tonnes, surpassing any other organic compound. Ethylene is currently produced from steam cracking of ethane, which produces vast quantities of CO2, contributing to global warming. Ethylene is the monomer for the most common plastic, polyethylene, and annual global production is approximately 80 million tons. Therefore, unlocking a sustainable or carbon neutral alternative to ethylene production is imperative. Ethylene has been produced in a wide variety of different microorganisms utilising the ethylene forming enzyme (EFE) from P. syringae pv phaseolicola. However, despite recent advances, substantial developments still need to be made to fully realise the potential of biological ethylene production in a self-sustaining chassis. Substantial improvements in ethylene production will need to address key bottlenecks such as enzyme solubility and biochemical precursor availability. We utilised a combination of systems biology, growth coupled competitive fermentation, mutagenesis and directed evolution to generate two strains with enhanced ethylene productivity. Both U2-25 and U3-26, had significant improvements in specific ethylene production. Omics investigations highlighted genomic mutations impacting glycolysis and the TCA cycle which may have been responsible for this improvement. However, further work is required to definitively conclude the role of these genomic alterations in regard to increased ethylene production.